Transcatheter arterial embolization of iatrogenic massive arterioportal fistula in the liver. (July 2022) - Okumura, Kenichiro; Kobayashi, Satoshi; Ogi, Takahiro; Sugiura, Takumi; Zhang, Yu; Kanatani, Mao; Yoneda, Norihide; Kitao, Azusa; Kozaka, Kazuto; Gabata, Toshifumi; Koda, Wataru
Background: Massive arterioportal fistula (APF) is naturally irreversible and can induce portal hypertension and portal vein thrombosis (PVT), worsening survival outcomes. Purpose: To evaluate the clinical course and details of transarterial embolization (TAE) procedures for massive APF. Material and Methods: This retrospective single-center observational study evaluated the time until embolization after puncture, imaging, embolization methods, and laboratory data of 10 consecutive patients who were diagnosed with massive APF after puncture and underwent TAE at our hospital from 1 April 2012 to 30 September 2019. Results: Out of 10 cases, eight demonstrated a simple type and the other two cases a complex network type on the digital subtraction angiography pattern of massive APF. In two simple-type cases for which re-embolization was required, other subsegmental branches were embolized. The two cases showing a complex network type had been embolized via not only the subsegmental branch, but also the extrahepatic and multiple subsegmental branches. Child–Pugh scores were improved in eight of the ten cases. PVT was seen in six cases before embolization, but disappeared after embolization in all cases, despite the fact that three cases had not received anticoagulant therapy. Six cases had digestive varices before embolization, suggesting portal hypertension, and two of the six cases with esophageal varices and one with gastric varices decreased after embolization. Conclusion: TAE for massive APF contributed to the improvement of hepatic reserve, the disappearance of PVT, and the improvement of portal hypertension; however, embolization of multiple branches may still be required in some cases.